The Rechtslehre doctrine and Kant's philosophy of history - Martins, Clélia Aparecida [UNESP] (Pontifícia Universidade Católica do Paraná (PUC-PR), 2012)
The text is divided in two phases. In the first phase, consisting of three parts, the main concepts of Kant's Doctrine of Right are considered in a comprehensive approach related to: the issue of the relations between natural right and positive right, problem closely connected to that of the relations between natural state and civil state, private right and public right; to the doctrine of property and its connection with political right. on treating the right in its several types, we intend to appoint the practical reasoning as a background of the Doctrine. In the second phase, concerning its last section, the consideration on the presence of the practical reasoning into the right is placed before some specificities of Kant's phylosophy of history, with the intent of establishing the possible relation between Rechtslehre and that philosophy.
Keywords: Doctrine of right; Freedom; Political right; Practical reasoning; Philosophy of history